Analysis of the Factors that Influence Precurrent Anxiety to Increase the Rate in Kesdam V / Brawijaya Malang - Raharjo; Koesnadi; Suhita, Byba Melda (Master of Public Health Program Universitas STRADA Indonesia, 2020)
In the framework of soldiers for promotion, they always experience anxiety, anxiety and sometimes not being able to sleep from all the soldiers, almost all of whom experience anxiety especially when faced with the pressure of the test that the captain will carry out for promotion, supported by the time needed to run self-actualization. Therefore, researchers are interested in examining the analysis of the factors that influence warriors' anxiety for promotion at the Military District V / Brawijaya Malang. The purpose of the study was to analyze the factors that influence warrior anxiety for promotion at the Military District V / Brawijaya Malang. The research design used is quantitative research with a cross sectional approach. Instrument data used questionnaire sheets using Ordinal Regression test. The results of the Ordinal Regression Test analysis say that p value = 0,000 for the readiness variable, p-value 0.174 for the Punishment variable and p-value 0.015 for the Reward variable. Then H0 is accepted and H1 is rejected, meaning that there is no influence of Readiness, Punisment and Reward on Warrior Anxiety to Increase Promotion in the Military District V / Brawijaya Malang. Based on the results of the Ordinal Regression Test analysis shows that the most influential variable is the readiness variable with a p-value of 0,000 <0,05, it is concluded that there is a significant influence between Warrior Readiness and Anxiety to Increase Rank in Military V / Brawijaya Malang. It is expected that respondents are able to control the anxiety they experience by increasing their readiness to become better